Reka Ulang Sebagai Alat Bukti Surat Oleh Penuntut Umum Dalam Perkara Pidana Berdasarkan Prinsip Due Process Of Law - Akhmad Zubairy (Scholar Center, 2021)
The purpose of this study is to discuss the urgency of re-enactment as evidence in evidence by the public prosecutor at trial and to find out whether the re-enactment reflects the principle of due process of law ? The research method used in this study is a normative research method. the results of the study can be drawn several conclusions. First, the urgency of re-enactment as evidence in evidence by the public prosecutor at trial is to give confidence to the panel of judges against the criminal events committed by the defendant. The public prosecutor tries so that the judge does not experience any more hesitation in deciding the case by representing a criminal event that actually occurred before the trial through a re-enactment mechanism. Second, the redesign has not fully reflected the principle of due process of law in general, but has not been able to fully accommodate it. This is because the regulations regarding reconstruction are still not clearly regulated, as well as which parties can follow suit.